Evaluation of the Indonesia Pintar Program at the Junior High School Level in Bandung Regency - Purnama, Randi; Dewi, Maya Puspita (Yogyakarta State University, 2024)
This study aims to evaluate the Indonesia Smart Program (Program Indonesia Pintar/PIP) at the junior high school (SMP) level in Bandung Regency. The evaluation adopts three key dimensions/indicators proposed by William N. Dunn to assess the implementation of PIP in Bandung Regency: (1) Effectiveness, (2) Efficiency, and (3) Equity. These dimensions were chosen due to recurring issues identified in the implementation of PIP. This research employs a qualitative approach with an instrumental case study design, utilizing multiple sources of information, including observations, interviews, audio-visual materials, documentation, and reports during the research process. The study focuses on PIP beneficiaries among junior high school students in Bandung Regency. The findings reveal the analysis of PIP in Bandung Regency based on effectiveness, efficiency, and equity. First, in terms of Effectiveness, PIP has succeeded in reducing the dropout rate among junior high school students but has not significantly increased the transition rate from basic to secondary education in Bandung Regency. Second, regarding Efficiency, PIP lacks regular and tiered socialization and monitoring by program implementers. Additionally, delays in fund disbursement to PIP beneficiaries are common. Third, in the aspect of Equity, the quota distribution for PIP is not allocated based on the distribution of dropout rates across sub-districts. This indicates persistent inequities and uneven distribution of PIP benefits to intended recipients.